.................................................................... 6
1. Oblicz wartość wyrażenia (y+3√2)² + y + 3√2 , dla y = _______
...................................................................2 - √2


....................................................................... 1 - √3
2. Oblicz wartośc liczbową wyrażenia (x - √3) (x+ √3) , dla x=_______
....................................................................... 1+ √12

1

Odpowiedzi

Najlepsza Odpowiedź!
2009-11-26T10:39:35+01:00
1. Oblicz wartość wyrażenia (y+3√2)² + y + 3√2 ,dla y = 6:(2 - √2)

y²+6√2y+18=
[ 6:(2 - √2)]²+6√2[ 6:(2 - √2)]+18=
=36:(4-4√2+2)+36√2:(2-√2)+18=
=36:(6-4√2)+36√2:(2-√2)+18=
=6-9:√2+18√2-36+18=-12-9√2:2+18√2=-12-13,5√2


2. Oblicz wartośc liczbową wyrażenia (x - √3) (x+ √3) ,
dla x=(1 - √3):( 1+ √12)

(x - √3) (x+ √3)=x²-3

[(1 - √3):( 1+ √12)]²-3=[(1-2√3+3):(1+2√12+12)]-3=
=(4-2√3):(13+4√3)-3=
=[(4-2√3)(13-4√3):(13+4√3)(13-4√3)]-3=
=[52-16√3-26√3+24]:[13-12]-3=
=76-42√3-3=73-42√3
1 5 1